2016
DOI: 10.1016/j.supflu.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of viscosities and densities of mixtures carbon dioxide+1-allyl-3-methylimidazolium chloride. Viscosity correlation

Abstract: The effect of viscosity reduction caused by the solubilization of CO2 is studied in order to improve the biomass processing in ionic liquids. To do so, densities and viscosities of the pure ionic liquid 1-allyl-3-methylimidazolium chloride and its mixtures with CO2 up molar fractions of 0.25 and temperatures between 333 and 372 K have been experimentally determined. Viscosities were correlated as a function of temperature and CO2 molar fractions with an average relative error of 2.5%. The viscosities of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, only a few viscosity data of mixtures CO 2 + IL can be found in literature [124][125][126] for non-cellulose dissolving ILs, and for the mixture CO 2 + [Amim]Cl [127]. In general, the reduction in viscosity is between 85% and 45% at moderate pressures of 10-12 MPa, but with molar fractions as low as 10% of CO 2 , viscosity can decrease 30-40% with respect to the viscosity of the pure IL.…”
Section: Viscosity Of Concentrated Cellulose Solutions In Ilsmentioning
confidence: 99%
“…To the best of our knowledge, only a few viscosity data of mixtures CO 2 + IL can be found in literature [124][125][126] for non-cellulose dissolving ILs, and for the mixture CO 2 + [Amim]Cl [127]. In general, the reduction in viscosity is between 85% and 45% at moderate pressures of 10-12 MPa, but with molar fractions as low as 10% of CO 2 , viscosity can decrease 30-40% with respect to the viscosity of the pure IL.…”
Section: Viscosity Of Concentrated Cellulose Solutions In Ilsmentioning
confidence: 99%
“…In this work, densities for the system CO 2 + [Emim][DEP] were obtained from Reference 20. For the system CO 2 + [Amim][Cl], densities were taken from Reference 11. For the system CO 2 + [Bmim][Cl], densities were approximated to those for the pure IL 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Since solubility of IL into CO 2 is negligible, no contamination from the former is produced. Other additional advantage is that dissolved CO 2 in IL can improve its transport properties (i.e., reducing the viscosity) 11,12 or decreasing the melting point, 13,14 which enhances the liquid window. For example, Lopes et al 8 demonstrated that addition of CO 2 improves the kinetics of the acetylation of cellulose in allylmethylimidazolium chloride ([Amim][Cl]) as well as the quality of the product.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for binary mixtures of BmimCl with ethanol or water, the said properties were also determined at 298.15 K and atmospheric pressure. Lopes et al [15] studied the reduction in the viscosity of the ionic liquid AmimCl caused by dissolution of CO2.…”
Section: Introductionmentioning
confidence: 99%